Safety and activity of blinatumomab for adult patients with relapsed or refractory B-precursor acute lymphoblastic leukaemia: a multicentre, single-arm, phase 2 study - Topp, Max S.; Nagorsen, Dirk (The lancet. Oncology, 2015)
Background: Adults with relapsed or refractory B-precursor acute lymphoblastic leukaemia have an unfavourable prognosis. Blinatumomab is a bispecific T-cell engager antibody construct targeting CD19, an antigen consistently expressed on B-lineage acute lymphoblastic leukaemia cells. We aimed to confirm the activity and safety profile of blinatumomab for acute lymphoblastic leukaemia. Methods: In a multicentre, single-arm, open-label phase 2 study, we enrolled adult patients with Philadelphia-chromosome-negative, primary refractory or relapsed (first relapse within 12 months of first remission, relapse within 12 months after allogeneic haemopoietic stem-cell transplantation [HSCT], or no response to or relapse after first salvage therapy or beyond) leukaemia. Patients received blinatumomab (9 μg/day for the first 7 days and 28 μg/day thereafter) by continuous intravenous infusion over 4 weeks every 6 weeks (up to five cycles), per protocol. The primary endpoint was complete remission (CR) or CR with partial haematological recovery of peripheral blood counts (CRh) within the first two cycles. Analysis was by intention to treat. This trial is registered at ClinicalTrials.gov, number NCT01466179. Findings: Between Jan 13, 2012, and Oct 10, 2013, 189 patients were enrolled and treated with blinatumomab. After two cycles, 81 (43%, 95% CI 36-50) patients had achieved a CR or CRh: 63 (33%) patients had a CR and 18 (10%) patients had a CRh. 32 (40%) of patients who achieved CR/CRh underwent subsequent allogeneic HSCT. The most frequent grade 3 or worse adverse events were febrile neutropenia (48 patients, 25%), neutropenia (30 patients, 16%), and anaemia (27 patients, 14%). Three (2%) patients had grade 3 cytokine release syndrome. Neurologic events of worst grade 3 or 4 occurred in 20 (11%) and four (2%) patients, respectively. Three deaths (due to sepsis, Escherichia coli sepsis, and Candida infection) were thought to be treatment-related by the investigators. Interpretation: Single-agent blinatumomab showed antileukaemia activity in adult patients with relapsed or refractory B-precursor acute lymphoblastic leukaemia characterised by negative prognostic factors. Further assessment of blinatumomab treatment earlier in the course of the disease and in combination with other treatment approaches is warranted.